Glycosaminoglycans as Novel Targets for in vivo Contrast-Enhanced Magnetic Resonance Imaging of Atherosclerosis - Uca, Yavuz O; Taupitz, Matthias (Journal of Cardiology and Cardiovascular Medicine, 2020)
Atherosclerosis is an important promoter of cardiovascular disease potentiating myocardial infarction or stroke. Current demand in biomedical imaging necessitates noninvasive characterization of arterial changes responsible for transition of stable plaque into rupture-prone vulnerable plaque. in vivo contrast enhanced magnetic resonance (MR) imaging (MRI) allows quantitative and functional monitoring of pathomorphological changes through signal differences induced by the contrast agent uptake in the diseased vessel wall, therefore it is the ideal modality toward this goal. However, studies have so far focused on the cellular targets of persisting inflammation, leaving extracellular matrix (ECM) far behind. In this review, we portray ECM remodeling during atherosclerotic plaque progression by summarizing the state of the-art in MRI and current imaging targets. Finally, we aim to discuss glycosaminoglycans (GAGs) and their functional interactions, which might offer potential toward development of novel imaging probes for in vivo contrast-enhanced MRI of atherosclerosis.